Análisis a los Estados Financieros de la Compañía de Transportes de Combustibles Loja S.A. COTRANSCOLSA. Periodos 2020 – 2021 - Añazco Merchan, Jenniffer Geanella (2023)
The Curricular Integration work named " Financial Statements Analysis of the Fuels Transport Company Loja S.A. COTRANSCOLSA. Periods 2020 - 2021", allows to achieve with the objectives set by carrying out the Vertical, Horizontal Analysis and the application of Financial Indicators, in order to determine the economic situation of the company. Regarding the vertical analysis applied to the Financial Statement Position, it is evident that the company is made up mostly of the group of non-current assets equivalent to 54.53% (2020) and 37.42% (2021), where the property plant and equipment account are the main assets that the company has; on one hand, the group of current liabilities that are equivalent to 0.14% (2020) and 24.49% (2021). On the other hand, in equity, for the subscribed capital that in 2020 is equivalent to 79.52% and for 2021 55%. The horizontal analysis allowed to know the variations that the accounts have suffered during these two periods, where it showed that inside the assets the group that presented the most variation is that of current assets, which includes cash and cash equivalents, within liabilities and equity, the group with the greatest variation was current liabilities and profit for the year. According to the income statement, the accounts with the greatest variation were income from ordinary activities and the administrative expenses account as part of the expenses. Finally, the financial indicators were applied where it is evident that the company has enough liquidity to cover its debts; a low indebtedness, it means, the lower the risk it has with its creditors; prudent levels in its activity indicators, and lastly extremely low profitability compared to other companies in its sector, due to its high costs.